Video Profile Pemasaran Destinasi Wisata Arung Jeram Desa Rantau Nipis Kec. Banding Agung Oku Selatan - Afta Apriansyah; Mardian Herri Pratama; Desy Misnawati (Yayasan Literasi Sains Indonesia, 2022)
Rantau Nipis is a village located in the District of Banding Agung, South Ogan Komering Ulu Regency, South Sumatra, Indonesia. This village has a postal code of 32274. This village has a population of 1,391 people consisting of 696 men and 695 women. The population of Lime overseas includes various tribes, including the Ogan Tribe, the Semende Tribe, the Java Tribe and the Ranau Tribe. Most of the community's income is from agriculture and fishing. Rantau Jeruk Nipis Village includes tourist areas including white water rafting which is centered on a lake located in Rantau Jeruk Nipis Village, there is a play area for young people to relax, a micro power plant and other areas. Rantau Nipis Village is a village with great tourism potential. Rantau Nipis is a village that has a lot of tourism objects, tourism objects need to be explored and seen with the help of video recording facilities so that this village has audiovisual recordings or can be called videos to attract tourism for the community or visitors.